INTEGRASI CUSTOMER RELATIONSHIP MANAGEMENT EFFECTIVENESS (CRME) DALAM PENERAPAN STRATEGI KOMUNIKASI PEMASARAN - Wayan Supada (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
The scipe of marketiing communication is devided into internal and external marketing communication. Internal marketing communication is carried out to build relationship between companies and the organizations within them, including shareholders, employess and stake holders in the company. While external marketing communications aims to build a corporate image and strong relationships between companies with other parties including consumers and the public at large. CRM is one of the strategies that can help maximize the objectives of marketing communications carried out by companies relating to products and services. The integration of the CRME model allows companies to manage relationships with customers so that an effective relationship management focus is achieved based on mapping of elements of IT, relationship marketing dan organizational climate.